Meckel’s diverticulum perforation into subumbilical median abdominal wall: a case report - Oricchio, Dario; Russo, Giulia; Angeloni, Riccardo; Battaglia, Benedetto; Sagnotta, Andrea; Belardi, Augusto; Solinas, Luigi; Mancini, Stefano (Acta Biomedica Atenei Parmensis, 2024)
Meckel’s diverticulum is a congenital anomaly due to the lack of atrophy of the yolk duct. It’s typically located in the distal ileum, and it is made up of all three layers of the ileal wall. Surgical treatment is indicated for symptomatic cases. As far as asymptomatic patients are concerned, the option of performing surgery remains controversial and the possible presence of risk factors should be considered. We present a case report of a 59-year-old man who went to the emergency room reporting abdominal pain radiating to the lower quadrants. Contrast-enhanced abdomen computed tomography revealed the presence of a tubular structure with a thickened and contrast-enhanced wall; thus, a radiological diagnosis of Meckel’s diverticulum was made. A laparoscopic surgical procedure was performed. The postoperative course was complicated by an abscess of the abdominal wall, which was healed thanks to ultrasound-guided drainage, surgical toilet, and targeted antibiotic therapy. The symptomatic diverticulum can be mistaken with appendicitis, in our case a preoperative diagnosis was possible, which allowed a surgical indication.